Physical Activity and Its Association With Body Mass Index: A Cross-Sectional Analysis in Middle-Aged Adults From 4 Sub-Saharan African Countries - Monica Mut; Lisa J. Ware; Lisa K. Micklesfield; Michele Ramsay; Godfred Agongo; Palwende R. Boua; Isaac Kisiangani; Ian Cook; Francesc Xavier Go´mez-Olivé; Nigel J. Crowther; Chodziwadziwa Kabudula; Shane A. Norris; et al. (My University, 2023)
Background: This study aimed to explore association of self-reported physical activity domains of work, leisure, and transport-related physical activity and body mass index (BMI) in 9388 adult men and women from the Africa-Wits-INDEPTH partnership for Genomic (AWI-Gen) study in Africa. Africa-Wits-INDEPTH partnership for Genomic is a large, population-based cross-sectional cohort with participants from 6 sites from rural and urban areas in 4 sub-Saharan African countries. Methods: A sex-stratified meta-analysis of cross-sectional data from men and women aged 29–82 years was used to assess the association of physical activity with BMI. Results: Overall, meeting physical activity guidelines of at least 150 minutes per week was associated with 0.82 kg/m2 lower BMI in men (β = −0.80 kg/m2 ; 95% confidence interval [CI], −1.14 to −0.47) and 0.68 kg/m2 lower BMI in women (β = −0.68 kg/m2 ; 95% CI, −1.03 to −0.33). Sex and site-specific differences were observed in the associations between physical activity domains and BMI. Among those who met physical activity guidelines, there was an inverse association between transport-related physical activity and BMI in men from Nanoro (Burkina Faso) (β = −0.79 kg/m2 ; 95% CI, −1.25 to −0.33) as well as work-related physical activity and BMI in Navrongo men (Ghana) (β = −0.76 kg/m2 ; 95% CI, −1.25 to −0.27) and Nanoro women (β = −0.90 kg/m2 ; 95% CI, −1.44 to −0.36). Conclusions: Physical activity may be an effective strategy to curb rising obesity in Africa. More studies are needed to assess the impact of sex and geographic location-specific physical activity interventions on obesity.
Keywords: obesity, MVPA, physical activity domain, Africa